ERGOMETRIC CRITERIA FOR MAXIMUM ANAEROBIC POWER OF HIGH QUALIFIED FOOTBALL PLAYERS - Samborskiy, A.G.; Sokorev, V.V.; Rutskoy, I.A.; Zhdanov, V.N. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze the speed-strength abilities of highly qualified football players. Methods and structure of the study. The experiment involved 29 players from two football clubs in the Russian Premier League. The maximum anaerobic power (MAP) of the athletes was determined using bicycle ergometry using a Monark bicycle ergometer. The running speed was recorded using the speedographic method, which allows continuous real-time recording of the running speed curve throughout the entire distance. Results and conclusions. The conducted research showed that the level of speed-strength abilities of highly qualified football players is at the average level. This suggests that athletes have a reserve that coaches should work on. In the operational control of the speed-strength readiness of football players, it is recommended to use an ergometric analysis of running speed, which makes it possible to determine informative indicators that characterize various aspects of running performance. Based on such an analysis, it is possible to make adjustments when designing training programs by selecting special exercises for developing lagging abilities.